2019
DOI: 10.1111/jpet.12393
|View full text |Cite
|
Sign up to set email alerts
|

Trust, ability‐to‐pay, and charitable giving

Abstract: In the literature on privately provided public goods, altruism has been motivated by what contributions can accomplish (public goods philanthropy), by the pleasure of giving (warm-glow philanthropy), or by the desire to personally make a difference (impact philanthropy).Underlying these motives is the idea that individuals trust that their donations reach their goal. We revisit these models but allow for distrust in the institutional structuresinvolved. An important result we derive is that trust consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Andreoni [10,[19][20] proposed that people are impure altruists who cooperate, not only because they care about a cause, but also because they gain additional personal utility from the act of giving itself: warm-glow. This hypothesis is supported by a large number of lab and eld based studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], with warm-glow: (i) increasing proportionally with the amount donated [22,25], (ii) motivating increased effort [33], (iii) being experienced more strongly with property rights (when the person donates money they have earned rather than won) [36], (iv) observed cross-culturally [29], (v) identi ed as an individual rather than a group based experience [37], having a neural basis located in the reward centres of the brain [26] and (vi) sustainable over time with repeat acts of generosity [32].…”
Section: Warm-glow and The Problem Of Cooling Cooperatorsmentioning
confidence: 72%
See 1 more Smart Citation
“…Andreoni [10,[19][20] proposed that people are impure altruists who cooperate, not only because they care about a cause, but also because they gain additional personal utility from the act of giving itself: warm-glow. This hypothesis is supported by a large number of lab and eld based studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], with warm-glow: (i) increasing proportionally with the amount donated [22,25], (ii) motivating increased effort [33], (iii) being experienced more strongly with property rights (when the person donates money they have earned rather than won) [36], (iv) observed cross-culturally [29], (v) identi ed as an individual rather than a group based experience [37], having a neural basis located in the reward centres of the brain [26] and (vi) sustainable over time with repeat acts of generosity [32].…”
Section: Warm-glow and The Problem Of Cooling Cooperatorsmentioning
confidence: 72%
“…These studies show the real power of warm-glow as a proximal mechanism to sustain cooperation beyond the lab. While extensively supported by evidence from lab based studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] experimental evidence that warm-glow is effective with respect to real world cooperation is lacking, and these studies ll these gaps. Further, these studies show not only that there is something special about the concept of warm-glow, compared to general positive affect, but also that this has long-term bene ts is terms of sustaining cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Social scientists have endeavored for decades to untangle the threads of utility and altruism as motivators of giving, asking in particular what differentiates between giving by those who have versus those who do not. Some of this work has found that individuals of low social economic status are motivated to perform prosocial behaviors like charitable giving by compassion or a disposition toward fellow feeling (Piff et al, 2010; Stellar et al, 2012), whereas those of higher economic standing are more likely to make decisions about giving based on calculations of reputation and pride (Kraus & Callaghan, 2016)—or, as has become fashionable, on carefully researched calculations of general utility in the form of impact giving (Ferrara & Missios, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The general hypotheses of warm-glow theory are supported by a large body of studies [23][24][25][26][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] which is summarized in Fig. 1a.…”
mentioning
confidence: 80%